Pandangan Tokoh Masyarakat Terhadap Nikah Hamil Di Desa Seuneubok Teungoh Dalam Perspektif Kesetaraan Gender - Siti Samra; Badrul Munir; Aulil Amri (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2025)
The phenomenon of pregnant women marrying outside of wedlock remains prevalent and draws significant attention in Indonesian society, including in Seuneubok Teungoh village. Ideally, the process leading to marriage should follow customary stages and religious recommendations. However, this is often bypassed as marriages are conducted abruptly without preparation from both parties, primarily to conceal disgrace, preserve family reputation, and uphold village dignity. This study aims to analyze community leaders' perspectives on marriages resulting from premarital pregnancy from a gender equality perspective. Employing empirical research with a phenomenological approach, data were collected through in-depth interviews, field observations, and simple documentation. The findings indicate that most community leaders view marriage as the sole solution to cover shame. However, women are more frequently discriminated against, face social stigma, and receive dowries deemed inadequate compared to customary practices, rendering them seemingly devalued for a mistake committed by both parties. It can be concluded that marriages conducted to conceal the shame of premarital pregnancy reinforce gender inequality. Therefore, a paradigm shift and societal system changes are necessary to address similar cases.